PERBEDAAN POLA ASUH ORANG TUA MENIKAH USIA DINI DAN USIA DEWASA - Dewi Anggraini; Tantri Wenny Sitanggang; Oryza Intan Suri (Politeknik Kesehatan Kementerian Kesehatan Banten, 2021)
More than 700 million women living now got married when they were still children. One of three has been married before they are 15 years old. Early marriage has impacts on the children’s development and parenting styles. Parenting styles are ways of parents to educate the children. These ways are embodiments of parents’ love and responsibility. Parents marrying early are going to cause less satisfying parenting style as they are not psychologically prepared enough to live the family lives and to perform their roles as parents. All of these enable them to mistakenly nurture their children. This research aimed at observing the different parenting styles between parents who married early and who married in adulthood age in operational territory of Pondok Aren Subdistrict, South Tangerang in 2020. This research design applied quantitative approach using comparative methods or comparison using T-Test Independent statistics test. The results show that p value = 0.025 or p < 0.05. From the value we can coclude that there were differences in parenting style between parents who marry early and who marry in adulthood age in operational territory of Pondok Aren Subdistrict. This is suggested to the Health Agency to collaborate with Community Health Centers, public figures, and village agencies to conduct marriage counselling about the appropriate parenting styles to the couples who has married early, such as taking care children’s needs based on their ages.